The effectiveness of the amazing geometry AR application for solid geometry learning - Widiyanti, Arum; Ratnasari (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Learning mathematics, particularly in the area of solid geometry, is often perceived as difficult by elementary school students, which highlights the need for appropriate learning media to support their understanding. This study aims to examine the effectiveness of learning media based on the Amazing Geometry Augmented Reality application in introducing solid geometry concepts to students. The research employed a pre-experimental design using a one-group pre-test and post-test. The population and sample consisted of all fifth-grade students at SDN Margodadi, totaling 11 students, selected through saturated sampling. Data were collected using essay tests that had undergone content and empirical validation, as well as reliability testing. Data analysis involved descriptive statistics, a normality test, and a paired sample t-test using IBM SPSS 26. The results showed that the average post-test score was higher than the pre-test score. The paired sample t-test indicated a t-count value of 15.486, which was greater than the t-table value of 1.812, with a significance level (2-tailed) of less than 0.05. These findings demonstrate that the use of the Amazing Geometry Augmented Reality application has a significant positive impact on students’ understanding of solid geometry. Overall, this study suggests that integrating augmented reality into mathematics instruction can enhance the learning process, particularly in the introduction of spatial concepts, and offers valuable implications for the broader use of technology in elementary mathematics education.